(untitled) (Academia Journal of Medicine, 2025)
Platelet-rich fibrin has emerged as an innovative biomaterial in dentistry, known for its regenerative properties that facilitate healing in various oral procedures. This review examines PRF’s clinical applications, efficacy, and mechanisms of action in dental treatments, including oral surgery, periodontics, and implantology. PRF is derived from the patient’s own blood, enhancing biocompatibility and reducing the risk of adverse reactions. Current research indicates that PRF contributes to improved soft and hard tissue healing, reduces postoperative complications, and enhances implant stability. Despite its promising potential, challenges such as variability in preparation protocols and the need for standardized clinical guidelines persist. This review advocates for continued research to optimize PRF application and to establish best practices in dental medicine.